Crystallization and preliminary X-ray analysis of isomaltase from Saccharomyces cerevisiae - Yamamoto, Keizo (International Union of Crystallography, 2008)

(untitled)
Isomaltase from Saccharomyces cerevisiae is an oligo-1,6-glucosidase that preferentially hydrolyzes isomaltose, with little activity towards isomaltotriose or longer oligosaccharides. An amino-acid sequence analysis of the isomaltase revealed that it belongs to glucoside hydrolase family 13. Recombinant isomaltase was purified and crystallized by the hanging-drop vapour-diffusion method with PEG 3350 as the precipitant. The crystals belonged to space group C2, with unit-cell parameters a = 95.67, b = 115.42, c = 61.77 Å, β = 91.17°. X-ray diffraction data were collected to 1.35 Å resolution from a single crystal on a synchrotron-radiation source.